2021
DOI: 10.1080/21663831.2021.1875079
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonic effect on the thermally activated migration of {101̄2} twin interfaces in magnesium

Abstract: Using a recent linear scaling method that fully accounts for anharmonic thermal vibrations, we calculated the activation free energy for {1012} twin boundary migration in magnesium up to 450 K, under both resolved shear stresses and non-glide stresses resulting from c-axis tension. Comparing to direct molecular dynamics data, we show that the harmonic transition state theory unexpectedly overestimates the activation entropy above temperatures as low as 100 K, leading to underestimates of the nucleation time by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Section 4.1) but also at high temperatures. Moreover, anharmonicity may become important at high temperatures, requiring to use more precise approaches relying on thermodynamic integration [79,82,83]. These approaches are still too computationally expensive for ab initio calculations, particularly in the case of a kinked dislocation.…”
Section: Dislocation Velocity and Yield Stressmentioning
confidence: 99%
“…Section 4.1) but also at high temperatures. Moreover, anharmonicity may become important at high temperatures, requiring to use more precise approaches relying on thermodynamic integration [79,82,83]. These approaches are still too computationally expensive for ab initio calculations, particularly in the case of a kinked dislocation.…”
Section: Dislocation Velocity and Yield Stressmentioning
confidence: 99%
“…When viewed as threedimensional domains, these disconnections are "terraces," which nucleate, grow laterally, and coalesce to advance the twin boundary (25,26). Sato et al (29) and Spearot et al (25,26) also suggested that the disconnection nucleation and migration rates can be affected by a variety of parameters, such as shear stress, temperature, orienta tion, and structure. This predicted glide mechanism (assisted by a local shuffling) has been supported by several highresolution TEM (HRTEM) observations of coherent twin boundaries (CTBs) decorated with disconnections (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of plasticity, the present random stress environment can be generated and implemented in a dislocation dynamics framework [57,58] to study for instance the competition between solid-solution and precipitation hardening in complex alloys. Beyond dislocations, any stress-induced microstructural process, such as the migration of twin interfaces [59] and other grain boundaries, could also be modeled in random alloys, accounting for the strong anisotropy of the correlations evidenced in the present study. Finally, using the expression of the mean-square displacement u 2 given in Ref.…”
Section: Discussionmentioning
confidence: 99%